Mathematics Literacy Ability Reviewing From Mathematic Reasoning On Students With Special Needs At Siyono 1 State Primary School - Danuri Danuri; St. Budi Waluya; Sugiman Sugiman; Y.L. Sukestiyarno; Rianisa Scientisa A (Universitas Negeri Semarang, 2022)
This research aims to investigate 1) students’ understanding of mathematical literacy. 2) Mathematical literacy level based on the mathematical reasoning of students with special needs (SSN) 3) Influencing factors. 4) learning process. 5) problems experienced. 6) Solutions to improve it for SSN This research was qualitative research. Data obtained through interview, quesionaire, test and documentation. The analysis techniques were data gathering, presentation, reduction, and conclution drowing or veryfiying. The data validity used triangulation techniques and sources. The findings show that 1) 3 regular students catagorized good, 1 regular students and 1 SSN were less good. 2) regular students were able to present statments, manipulate mathematics, and conclude logically while the SSN were not. 3) students’ understanding level, motivation and assitance. 4) motivation building, exercises, lecturing method. 5) no inclusive teacher, students’ low understanding, motivation and literacy level. 6) teacher traning, special assistance, exercises, lecturing method and giving trick and easy way.